Antagonist activity of Trichoderma harzianum against Sclerotinia sclerotiorum from common bean - Costa Carvalho, Daniel Diego; Pereira Costa Muniz, Paulo Henrique; Martins, Irene; Alves Santos de Oliveira, Thiago; Corrêa Marques Mello, Sueli (Acta Iguazu, 2019)
A key point in the development of new biopesticides is the discovery of strains with greater activity or more adapted to the environmental conditions under which such products are used. Thus, there is need to maintain a continuous flow of characterization and assessment of biocontrol agents. Therefore, five Brazilian Trichoderma harzianum isolates were evaluated in vitro against Sclerotinia sclerotiorum, the causal agent of the white mold of common bean. Initially, the isolates grown with the pathogen by paired culture and antibiosis assays. Light microscopy studies showed mycoparasitism by isolate CEN316 on S. sclerotiorum hyphae. Besides, reductions in the mycelial growth of S. sclerotiorum were verified with non-volatile metabolites of T. harzianum, wherein CEN287 and CEN316 inhibited the pathogen growth in 95% and 90% respectively. In vitro results, credit such isolates as potential holders in the development of soil inhabitant pathogens biological control program.